Balance impairment does not necessarily coexist with gait apraxia in mild and moderate Alzheimer’s disease - Pereira, Fernando Vieira; Oliveira, Fabricio Ferreira de; Schultz, Rodrigo Rizek; Bertolucci, Paulo Henrique Ferreira (Arquivos de Neuro-Psiquiatria, 2016)
Currently, there are no studies reporting how much balance impairment coexists with gait apraxia in mild and moderate Alzheimer’s disease (AD). Objectives To assess correlations among gait apraxia, balance impairment and cognitive performance in mild (AD1, n = 30) and moderate (AD2, n = 30) AD.Method The following evaluations were undertaken: gait apraxia (Assessment Walking Skills); balance performance (Berg Balance Scale); Clinical Dementia Rating and Mini-mental State Examination (MMSE).Results While disregarding AD subgroups, Berg Balance Scale and the MMSE correlated significantly with Assessment Walking Skills and 23% of all subjects scored below its cut-off. After stratification, Berg Balance Scale correlated significantly with Assessment Walking Skills in both AD subgroups, and with the MMSE only in AD1.Conclusions Balance impairment does not necessarily coexist with gait apraxia. Gait apraxia is more prevalent in moderate AD when compared with mild AD.
Keywords: Alzheimer disease; gait; apraxias; postural balance